What to Believe? Impact of Knowledge and Message Length on Neural Activity in Message Credibility Evaluation - Kwasniewicz, Lukasz; Wojcik, Grzegorz M.; Schneider, Piotr; Kawiak, Andrzej; Wierzbicki, Adam (Frontiers in Human Neuroscience, 2021)
Understanding how humans evaluate credibility is an important scientific question in the era of fake news. Message credibility is among crucial aspects of credibility evaluations. One of the most direct ways to understand message credibility is to use measurements of brain activity of humans performing credibility evaluations. Nevertheless, message credibility has never been investigated using such a method before. This article reports the results of an experiment during which we have measured brain activity during message credibility evaluation, using EEG. The experiment allowed for identification of brain areas that were active when participant made positive or negative message credibility evaluations. Based on experimental data, we modelled and predicted human message credibility evaluations using EEG brain activity measurements with F1 score exceeding 0.7.